Health benefits of aerobic exercises on overweight female young adults / Maisarah Shari - Shari, Maisarah (2013)
The prevalence of overweight and obesity has increased dramatically worldwide with an estimate of 62 percent of young female adults in Malaysia until 2010. Aerobic exercise are strongly recommended to promote overall physiological health in oneself, preventing and reducing risks of health tribulations. Lack of study conducted in comparing between land-based and water-based aerobic dance on overweight population. The aims of this study were to determine the effects of aerobic and aqua dance exercises on blood pressure (BP), blood glucose (BG), blood lipids (BL), body composition (BC), muscular strength (MS), and cardiorespiratory fitness (CF) and to determine which type of aerobic exercise is the best in improving overall health parameters among overweight female young adults. A total of 75 overweight females participated in this study and were randomly assigned to interventions and control groups (25 aerobic dance, 25 aqua dance, 25 control). The health parameters were assessed using mercury sphygmomanometer (BP), blood sampling (BG and BL), body weighing, body mass index, waist to hip circumference and skinfold thickness measurements (BC), grip dynamometers (MS), submaximal cycle ergometer with Astrand Rhyming protocol (CF). Intervention groups engaged in aerobic exercises workout (aerobic dance and aqua dance) for nine weeks, three times per week and one hour per session. All health parameters were measured at baseline, week five, and at post-exercise. Significant improvements on all health parameters measured were noted in both training groups across observations periods (/k 0.05). Aqua dance demonstrated greater improvement in BP, BL, BC, and MS compared to aerobic dance (/k 0.05). In conclusion, aqua dance exercise is more beneficial and a safer type of aerobic exercise as compared to aerobic dance exercise as a means to enhance multiple aspects of health in overweight female young adult.